Inside the mouth of sharks: Comparative data on the morphology of the oropharyngeal cavity - Poscai, Aline N. [UNESP]; Casas, André Luis S. [UNESP]; da Silva, João Paulo C.B.; Lenktaitis, P.; Gadig, Otto B.F. [UNESP] (Elsevier, 2021)
Oropharyngeal dermal denticles and oral papillae are present throughout the oropharyngeal cavity, and incorporate the use of taste buds to orally process and evaluate the food items, whereas oral denticles are thought to provide a form of protection against abrasion during food consumption and improve ventilation efficiency. Herein, are compared the microstructure of the oropharyngeal denticles and papillae of large predatory requiem sharks (Carcharhinidae) (Carcharhinus brevipinna, C. leucas, C. limbatus, C. obscurus, C. signatus, and Galeocerdo cuvier), under scanning electron microscopy. The results revealed that the largest oral denticles were found in adults of C. signatus, followed by juveniles of G. cuvier, C. leucas, and C. obscurus, respectively. Oral papillae were found to be larger in G. cuvier, C. signatus, and in C. leucas, and all these specimens presented round-shaped papillae. The higher denticles densities were found in the oral cavity of C. signatus, however, this species presented the lowest density of papillae. Carcharhinus limbatus presented the second highest rate of denticles density, followed by G. cuvier, C. obscurus, C. leucas, and C. brevipinna. The highest density of papillae was found in C. brevipinna, indicating that the density of denticles is inversely proportional to the papillae distribution, the same as we observed in C. signatus. The denticles density seems to be higher as the animal increases in size, as we observed in adult specimens of C. signatus, and this shark presented two different morphologies of denticles, different from the other species studied here. This may suggest that densities and sizes of these structures differ as the animals grow, expressed by the prey spectrum availability and the dietary shifts due to the distinct habitat which the species are associated during their life cycles.
Keywords: Carcharhiniformes; Oral denticles; Papillae; Scanning electron microscopy